The Mausoleums of Fatima Khatun and al-Ashraf Khalil - Hassan, Naglaa Muhammad Sami (AUC Knowledge Fountain, 2019)
This thesis will conduct an architectural analysis of two nearly contemporary mausoleums situated on the northern tip of the Southern Cemetery of Cairo near the Sayyida Nafisa shrine. The Southern Cemetery is the oldest one, which stretches from the east at Muqattam hill to the south at Fustat. The mausoleums of the princess Fatima Khatun and al-Sultan al-Ashraf Khalil date to the late 13th century. Among the interesting aspects of the mausoleum of Fatima Khatun (Umm al-Salih), the wife of al-Mansur Qalawun, is its unique Maghribi style minaret. In addition, apart from his splendid mausoleum, al-Ashraf Khalil, Qalawun’s son, constructed other royal secular buildings in the Citadel. I relied on a number of primary and recent sources, notably the Comité Bulletins. This study also traces the efforts exerted by the Comité and contemporary projects to safeguard the monuments from the encroachment of secular buildings and the rising of the groundwater table. The area is privileged by its religious significance, its funerary function, and the historic imperial mausoleums. Considering its dense population and the dilapidated status from which the two Mamluk complexes have suffered, prompt action should be taken for a twofold purpose: to restore the missing parts of the cultural heritage as well as to encourage the residents to maintain it and raise their living standard at the same time.